Antral follícles count as predictor of ovarian response and FIV/ICSI results - Arce Benites, Miguel (2015)
Objective: To determine antral follicles count capacity in ovarian response and FIV/ICSI results prediction compared with women’s age and basal FSH and estradiol. Design: Retrospective study. Setting: Hospital Nacional Docente Madre Niño San Bartolome. Participants: Patients who had assisted reproduction techniques. Interventions: Study of all high complexity assisted fertilizations (FIV/ICSI) between January 2007 and December 2008. We reviewed all clinical charts, and both assisted reproduction and ultrasound unit databases. We included 49 cycles where we registered age, basal FSH and estradiol values, antral follicles count, number of aspired and mature follicles, clinical and ongoing pregnancies rates. For ovarian response predictive capacity statistical analysis we used regression and correlation coefficients and C4HI2 test in order to compare clinical and ongoing pregnancies rates. Main outcome measures: Correlation between number of aspired and mature oocytes, age and FSH values, and count of antral follicles. Results: Main patients age was 35,8 ± 4,6. We found significant positive correlation between aspired and mature oocytes and antral follicles count, significant negative correlation with age and FSH, significance being higher for antral follicles count in both cases. No ovarian response marker was associated with pregnancy rates. Conclusions: Antral follicle count at the beginning of treatment is a simple non invasive method and with best predictive power of ovarian response compared with age, basal FSH and estradiol, but without predictive power for pregnancy.